PERAN BUKU KOMIK DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Suparmi, Suparmi; Rahmawati, Putri; Widakdo, Ridwan; Gusparenady, Rachel Calista; Fathina, Rafa Azzahra (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
Students face various challenges in improving the quality and success of learning. Thus, a strong learning motivation factor is needed so that students are able to face learning challenges. The use of comic book media is one way to encourage students' interest in learning. The use of comic books as a learning medium has been widely implemented and the results have been proven to increase students' motivation to learn. The method used is in the form of literature study by searching, combining, and reviewing publications according to the topic of discussion. Data was taken from google scholar with the keyword "student learning motivation & comic books" in the time span from 2019 to 2024 and around 14,500 articles and 47 articles were obtained in accordance with the research theme. The results of the study show that comic books as a learning medium and increase students' motivation, help better understanding of topics and foster a positive attitude towards learning by providing an interesting and interactive learning experience.